Effect of Intrinsic Motivation on Employee Performance: A Case of Cooperatives in Kageshwori Manohara Municipality - Subedi, Sadhana; Ghimire, Shiva Raj (Nepalese Journal of Business and Management Studies, 2022)
Intrinsic motivation is one of the major tools to enhance employee performance in every sector. However, there has been less study regarding the case of the cooperative. Thus, the research study aims to investigate the effect of an intrinsic motivation scheme on employee performance in Kageshwori Manohara. The study’s specific objectives are: to identify the various types of non-monetary incentives and to find the effects of non-monetary incentives on employee performance. Alderfer’s ERG (Existence, Relatedness, and Growth) theory is used as a theoretical reference. Employee performance is taken as the dependent variable and intrinsic motivation as the independent variable, where intrinsic motivation is represented by recognition and career development. Data collection is done with the help of a structured questionnaire distributed among 120 students, out of which 104 students were taken as the final sample size. The research design embraced in the study consists of descriptive, relational, and casual research designs. Various tools used for data analysis were mean, median, standard deviation, correlation, and regression. The study concluded that career development and recognition have a positive and significant relationship with employee performance. Further, the study showed that cooperative employees are happy and satisfied with intrinsic motivation practices of their cooperative.